ANALYSIS OF ASCORBIC ACID STABILITY TO 20% BY USING SILICONE EMULSIONS DIFFERENT VEHICLES AND PRESERVATIVES - Sgarbi Aguiar Moriggi, Bruna; Granemann Nunes, Talita Regina; Marcheti, Marithsa Maiara (Anais eletrônicos do International Symposium on Science and Biotechnology, 2017)
Vitamin C has physiological effects on the skin such as: inhibition of melanogenesis, promotion of collagen synthesis and antioxidant action. The development of cosmetics containing vitamin C in the acid form presents difficulties inherent in their physico-chemical characteristics that prevent the stability of the final product. The objective of this study was to analyze the stability of 20% ascorbic acid in emulsions developed with different preservatives and still using water, propylene glycol or glycerin as vehicle. 5 formulations containing 20% ascorbic acid were prepared in silicone emulsions. The samples were analyzed at 0, 15, 30 and 45 days for organoleptic characteristics and ascorbic acid content. Samples 1 and 5 had a greater reduction in the content, possibly due to the fact that in both the water was used as the total vehicle of the emulsion. Tests 2.3 and 4 had lower content reduction, probably due to the use of a binary system containing only 10% water and glycerine or propylene glycol as the emulsion vehicle. Regarding preservatives, metabisulphite was not found to be effective against the oxidation of vitamin C in the presence of large amounts of water, since the sample 5 used metabisulfite and water as the total vehicle of the formulation and was one of the samples that presented the most decrease in the content of active principle.